Pengaruh Manajemen Aset Terhadap Kinerja Keuangan Perusahaan - Achmad, Noor; Hidayat, Lukman (LPPM Institut Bisnis dan Informatika Kesatuan, 2013)
Assets management is an ability of a company in managing all of its assets that take a leading role in a company’s operation and it can be expected to create benefit. The assets management will be able to show that the company is capable to control its performance efficiently and effectively. The objective of this study is to find out the influence of assets management (X) – utilizing indicators: TATO, FATO, and WCTO – to the company’s financial performance (Y) by indicator-OPM. This study was done at two manufacturing companies, PT Holcim Indonesia Tbk. and Astra International Tbk., in the period 2005 – 2010. To test the significance of the influence of assets management to the financial performance of the two companies, the author analyzes and measures the correlation and influence between the variables in this study, using correlation coefficient (r) and determination coefficient (r square) and regression coefficient (β). Based on the result of this study it can be found out that the assets management of PT Holcim Indonesia Tbk. and PT Astra International Tbk. by indicator-TATO has significant influence to OPM. By indicator-FATO, the assets management does not have significant influence to OPM. Assets management by indicator-WCTO does not have significant influence to OPM. The significant level is set at 0,10 or 10%. This insignificance of FATO and WCTO to OPM is due to the financial performance is financed by its total assets. Keywords: assets management; financial performance